2007
DOI: 10.1002/adfm.200600985
|View full text |Cite
|
Sign up to set email alerts
|

New Family of Ruthenium‐Dye‐ Sensitized Nanocrystalline TiO2 Solar Cells with a High Solar‐Energy‐Conversion Efficiency

Abstract: A new type of ruthenium complexes 6–8 with tridentate bipyridine–pyrazolate ancillary ligands has been synthesized in an attempt to elongate the π‐conjugated system as well as to increase the optical extinction coefficient, possible dye uptake on TiO2, and photostability. Structural characterization, photophysical studies, and corresponding theoretical approaches have been made to ensure their fundamental basis. As for dye‐sensitized solar cell applications, it was found that 6–8 possess a larger dye uptake of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…Adsorption of JJ-12 onto a TiO 2 electrode was observed to broaden the absorption band and to red shift the absorption threshold up to 770 nm, ensuring a good light-harvesting efficiency (Figure 2(b)). Such broadening and red shift have been observed in many ruthenium sensitizers on TiO 2 electrodes [25,26]. We also observed that the JJ-12 exhibited strong luminescence maxima at 740-755 nm when they were excited with their MLCT absorption bands at 298 K in an air-equilibrated ethanol solution.…”
Section: Resultssupporting
confidence: 77%
“…Adsorption of JJ-12 onto a TiO 2 electrode was observed to broaden the absorption band and to red shift the absorption threshold up to 770 nm, ensuring a good light-harvesting efficiency (Figure 2(b)). Such broadening and red shift have been observed in many ruthenium sensitizers on TiO 2 electrodes [25,26]. We also observed that the JJ-12 exhibited strong luminescence maxima at 740-755 nm when they were excited with their MLCT absorption bands at 298 K in an air-equilibrated ethanol solution.…”
Section: Resultssupporting
confidence: 77%
“…[21] The central Pt À N distance of the ligand fpbpy is shorter than those of the outer nitrogen atoms, mainly because of the steric demand as documented in the literature. [18] The Pt À Cl(1) distance of 2.314(3) is comparable to that of the other Pt II -chloride complexes. [22] Furthermore, complex 1 exhibited a head-to-tail stacking along the b axis of the crystal lattice, giving a zigzag [Pt] n metal chain with intermolecular Pt···Pt distances of 3.385 and a PtÀPtÀPt angle of 153.598.…”
Section: Synthesis and Characterizationmentioning
confidence: 75%
“…The required terdentate chelate fpbpyH was obtained by a Claisen condensation reaction employing 6-acetyl-2,2'-bipyridine and ethyl trifluoroacetate, followed by treatment with an excess of hydrazine hydrate in refluxing ethanol according to procedures reported in the literature. [16,18] This ligand has a high potential for forming the anionic tridentate chelate by facile deprotonation during the reaction with a transition-metal reagent in basic media.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…45,46 It has been shown that Ru(II) polypyridyl complexes perform very efficiently in DSSCs. [47][48][49][50][51][52][53] The complexes used for DSSCs exhibit interesting photophysical properties, such as light absorption across the visible spectrum and long excited-state lifetimes. [54][55][56][57] These properties make this class of complexes highly interesting as potential PS in PDT.…”
Section: Introductionmentioning
confidence: 99%